Evaluation of functional integrity of the retinohypothalamic tract in advanced glaucoma using multifocal electroretinography and light-induced melatonin suppression - Pérez-Rico, Consuelo; de la Villa, Pedro; Arribas-Gómez, Ignacio; Blanco, Román (Experimental eye research, 2010)
The aim of the study was to investigate the survival of melanopsin-expressing retinal ganglion cells (mRGCs) and the functional integrity of the retinohypothalamic tract in patients with bilateral advanced glaucomatous optic neuropathy by measuring the neuroendocrine light response of the pineal gland. Nine patients with bilateral advanced primary open-angle glaucoma (glaucoma group) and nine normal control subjects (control group) were included in this pilot observational, prospective, case-control study. The best-corrected visual acuity logMAR, standard automated perimetry mean deviation, and the retinal nerve fiber layer thickness determined by optical coherence tomography and multifocal electroretinography were used to evaluate the changes. Melatonin was analyzed in the saliva by radioimmunoassay before and after exposure to bright light (600 lux) for 60 min at night. The advanced glaucoma group did not have any significant nocturnal melatonin suppression after exposure to bright light (14.28 ± 3.07 pg/ml pre-light melatonin concentration vs. 15.22 ± 3.56 pg/ml after light exposure; p = 0.798) unlike the marked melatonin suppression in the control group (22.43 ± 4.37 pg/ml pre-light melatonin concentration vs. 11.25 ± 1.89 pg/ml after light exposure; p < 0.002). Response density estimates by the scalar product amplitude measure for the interval 0–80 ms of the first-order kernel responses were similar in both groups, indicating that outer retinal function was significantly unchanged in the glaucoma group (5.95 ± 0.54 nV/dg^2) compared with the control group (6.20 ± 0.22 nV/dg^2) ( p = 0.689). Our findings are consistent with the interpretation that the rhythmic secretion of melatonin was affected in advanced glaucoma, suggesting that attention should be paid to non-image-forming visual functions, such as control of circadian rhythm and the clinical impact in patients with glaucoma. ►Retinal ganglion cells (RGC) damage in glaucoma might result in melanopsin-RGC death. ►Melanopsin-RGC death leads to the alteration of rhythmic secretion of melatonin. ►Loss of synchronization of circadian rhythms and recurrent insomnia might be established.